Enhancement of Liquid and Gaseous Biofuels Production From Agro-Industrial Residues After Thermochemical and Enzymatic Pretreatment - Antonopoulou, Georgia; Kampranis, Anastasios; Ntaikou, Ioanna; Lyberatos, Gerasimos (Frontiers in Sustainable Food Systems, 2019)
In the present study, the effect of thermo-chemical pretreatment and enzymatic hydrolysis on the saccharification and the further bioconversion of two different types of lignocellulosic agro-industrial residues to bioethanol and methane, was investigated. The residues used were the sunflower straw (SS) and the cracked olive stones (OS) remaining after the olive oil production process. Biomasses were subjected to simultaneous chemical and thermal pretreatment using either dilute H2SO4 or dilute NaOH aqueous solutions of concentrations 0.5, 1, and 1.5% (w/v), at 121°C for 60 min. The saccharification of the complex carbohydrates due to pretreatment was determined in terms of the sugars released, and the effect of each pretreatment was evaluated statistically. The effect of the enzymatic hydrolysis of the biomasses using commercial cellulolytic enzymes on saccharification was also assessed and statistically evaluated in terms of different enzymatic loadings. Subsequently, the pre-treated wastes were used as a substrate for methane and ethanol production using mixed methanogenic consortia and the yeast Pachysolen tannophilus, respectively.